Penyusunan Studi Kelayakan Bisnis UMKM di Kota Daro II Kecamatan Rantau Panjang Kabupaten Ogan Ilir - Yulia Hamdaini Putri; Sulastri Sulastri; Marlina Widiyanti; Muhammad Kemas Husni Thamrin; Aslamia Rosa; Ahmad Syathiri (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2022)
Village communities have relatively low incomes but have abundant natural resources that can be exploited, such as wild plants, swamps, fertile land, and clean flowing rivers. On the other hand, although education is relatively low, rural communities have many skills and expertise that can be developed, for example in the village of farmers in Kota Daro II the majority of people are farmers, breeders and weavers. Thus, the community needs MSME assistance through proper business development learning. The preparation of a business feasibility study is a fundamental step in developing a better business. The problems faced by rural communities are the lack of community knowledge to be able to analyze problems such as environmental, marketing, social, legal, and finance as well as the lack of community knowledge for business management. This community service partner is a village community in Kota Daro II who works as a breeder and weaver. The method used is counseling and mentoring. The result of this activity is that the community can analyze the business aspects they are engaged in.